Developing and Piloting a Q-study on Pedagogical Challenges in Problem- and Project-based Learning for First-year Engineering Students - Lyngdorf, Niels Erik Ruan; Dahl, Bettina; Jiang, Dan (Proceedings from the International Research Symposium on Problem-Based Learning (IRSPBL), 2025)
Research highlights the benefits of Problem- and Project-Based Learning (PBL) for engineering education, but students face challenges with some of its pedagogical features. This pilot study uses Q-methodology to explore first-year engineering (FYE) students’ learning challenges in a PBL environment. Based on literature, feedback from PBL experts, the University Student Counselling and Well-being unit, and students, 39 Q- statements was developed regarding different pedagogical challenges of students in PBL. Rather than simply identifying challenges, this study aims to identify the most predominant ones. Q-methodology is appropriate because participants rank statements in relation to each other, instead of rating individual statements. Our Q sorting question therefore asks FYE students to rank pedagogical features of PBL from most to least significant in terms of perceived challenge in relation to learning. To pilot the Q, we consulted two experts in PBL and Q-methodology and subsequently let 5 FYE students do the sorting activity. The results of this pilot are informative in themselves in further developing the tool. In the long term, this study is anticipated to provide knowledge about how students struggle with PBL which will help universities become aware of and remedy the situation.